THE RELATIONSHIP OF MACROZOOBENTHOS ABUNDANCE WITH OIL AND METAL CONCENTRATIONS IN SEDIMENTS AROUND COASTAL WATERS INDUSTRIAL AREA OIL CITY OF DUMAI RIAU - Amiroh, Amiroh; Badrun, Yeeri; Retnawaty, Sri Fitria (Asian Journal of Aquatic Sciences, 2023)
Some studies say the pollution level in the waters oil industry in Dumai City, Riau. The level of pollution that occurs will affect the abundance of macrozoobenthos. This research aims to know the concentration of oil and heavy metals in sediments in the waters around the area of the Dumai City oil industry, knowing the effect of oil on the abundance of macrozoobenthos. This research method includes placement of research stations, observation and sampling, TSS sample analysis method, concentration oil in sediment samples, heavy metal concentrations of Pb, Cd, and Cu at sediment samples, macrozoobenthos abundance Analysis, and data analysis. Results research average concentration of oil in sediments in water areas The oil industry of Dumai City, Riau, has passed the threshold that has been set determined by the Department of Water Resources Quality Assurance/Quality Control Program That is > 1000 ppm, so it can be said that station 1 up to 9 are polluted and harmful to organisms that live on the bottom those waters relationship of oil concentration, heavy metals (Pb, Cd, and Cu) moderate to weak.